2000
DOI: 10.1177/00220345000790060601
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Degradation of Resin-Dentin Bonds in Humans Over 1 to 3 Years

Abstract: The longevity of resin restorations is currently an area of great interest in adhesive dentistry. However, no work has been conducted to investigate the durability of resin-dentin bond structures using human substrate in vivo. The purpose of this study was to investigate the degradation of the resin-dentin bond structures aged in an oral environment for 1, 2, or 3 years. Cavities were prepared in primary molars, and an adhesive resin system (Scotchbond Multi-Purpose) was applied to the cavity. After 1 to 3 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
417
1
126

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 551 publications
(586 citation statements)
references
References 19 publications
20
417
1
126
Order By: Relevance
“…Ideally, after acid-etching, the adhesive should completely infiltrate the delicate fibrillar network. Optimal resin infiltration is crucial to maximize bond strength [5,6] and bond durability [1], as unprotected collagen fibrils may be hydrolyzed over time [11,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, after acid-etching, the adhesive should completely infiltrate the delicate fibrillar network. Optimal resin infiltration is crucial to maximize bond strength [5,6] and bond durability [1], as unprotected collagen fibrils may be hydrolyzed over time [11,16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the adequate immediate bond strength, in vivo (12) and in vitro (13) studies have revealed that resindentin bonds deteriorate over time. It has been speculated that a decreasing concentration gradient of resin monomer diffusion within the acid-etched dentin, and a subsequent resin elution from hydrolytically unstable polymeric hydrogels within the hybrid layers (14) leave the exposed collagen fibrils susceptible to hydrolytic and enzymatic degradation, mediated by endogenous metalloproteinases (MMPs) (15).…”
Section: Introductionmentioning
confidence: 99%
“…However, marginal discoloration or recurrent caries are frequently found in clinical resin restoration for long-term use. Several in vivo [1][2][3][4] and in vitro studies [5][6][7][8] have shown the degradation mechanism of the bonds. However, information on bond degradation is very limited.…”
Section: Introductionmentioning
confidence: 99%
“…However, information on bond degradation is very limited. Degradation analysis has mainly been conducted with the use of water storage testing [5][6][7][8] or human 2,3 and monkey models. 1,4 However, in these test methods the disadvantage is that a long test span (i.e., months or years) is needed to obtain results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation